2017
DOI: 10.1590/1809-4430-eng.agric.v37n1p24-34/2017
|View full text |Cite
|
Sign up to set email alerts
|

Hymenaea courbaril SEEDLINGS IN PROTECTED ENVIRONMENTS AND SUBSTRATES

Abstract: ABSTRACT:The Brazilian copal is a tree fruit species that can be used for various purposes. The study evaluated protected environments and substrates in forming Brazilian copal seedlings (Hymenaea courbaril), at the State University of Mato Grosso do Sul, Cassilândia-MS, from January to March, 2014. Two greenhouses were used: (A1) agricultural greenhouse covered with aluminized thermal reflector screen of 50% shading and (A2) agricultural greenhouse covered with black screen of 50% shading. Inside the greenhou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…It also provided chemical elements for nutrition, promoting the satisfactory development of the Syzygium cumini seedlings, with larger dry masses. The same was observed for other fruits, such as Baru (Dipteryx alata Vog) (Costa et al, 2015), passion fruit (Passiflora edulis) (Lima et al, 2016), jatobá (Hymenaea courbaril) (Sanches et al, 2017) and mangaba (Hancornia speciosa) (Arrua et al, 2016). It was observed that the substrates containing 20 and 40% Bioplant ® (S11 and S13), as well as those containing 20, 30 and 40% fine sand (S3, S4, and S5), presented the lowest dry masses in Syzygium cumini plants (Table 5).…”
Section: Plant Growth and Developmentsupporting
confidence: 72%
See 1 more Smart Citation
“…It also provided chemical elements for nutrition, promoting the satisfactory development of the Syzygium cumini seedlings, with larger dry masses. The same was observed for other fruits, such as Baru (Dipteryx alata Vog) (Costa et al, 2015), passion fruit (Passiflora edulis) (Lima et al, 2016), jatobá (Hymenaea courbaril) (Sanches et al, 2017) and mangaba (Hancornia speciosa) (Arrua et al, 2016). It was observed that the substrates containing 20 and 40% Bioplant ® (S11 and S13), as well as those containing 20, 30 and 40% fine sand (S3, S4, and S5), presented the lowest dry masses in Syzygium cumini plants (Table 5).…”
Section: Plant Growth and Developmentsupporting
confidence: 72%
“…For other fruits has been reported the use of manure associated with vermiculite as favoring the formation of high-quality seedlings. For example, Baru (Dipteryx alata Vog) (Costa et al, 2015), passion fruit (Passiflora edulis) (Lima et al, 2016), jatobá (Hymenaea courbaril) (Sanches et al, 2017) and mangaba (Hancornia speciosa) (Arrua et al, 2016). For use a material as a substrate, some things must be considered like the species that will be cultivated and the time required for its growth which, added to the type of container, can limit the growth of the root system.…”
Section: Introductionmentioning
confidence: 99%
“…High quality seedlings must possess superior genetic quality, well formed, free of phytopathogenic organisms, without physical damages, free of weeds, low cost, easy handling and commercialization (Minami, 1995) associated to a robust and well distributed root system with low distribution of aerial and root phytomasses (desirable from 1 to 2), low relation height and stem diameter and higher quality Dickson indexes (Costa, et al, 2011, Costa et al, 2015, Arrua et al,2016, Sanches et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Maiores mudas em altura, com maior número de folhas, foram formadas na tela preta. Sanches et al (2017), https://doi.org/10.1590/1809-4430-eng.…”
Section: Resultados: O Desenvolvimento De Mudas Deunclassified